KERENTANAN WILAYAH PESISIR BERDASARKAN PARAMETER FISIK DAN SOSIAL EKONOMI DI KELURAHAN PELINTUNG KOTA DUMAI - Lady Jewlaika; Mubarak Mubarak; Trisla Warningsih (Jurnal Ilmu Lingkungan, 2022)
This research was conducted in March 2021, which is located on the coast of Pelintung Village, Dumai City, Riau Province. The purpose of this study is to calculate physical parameters using MCA (Multi Criteria Analysys) standards, socio-economic parameters using MCA standards, and analyzing vulnerability using Geographic Information Systems. The research method used was purposive sampling, using a sample measurement technique based on the Slovin formula and the data obtained were secondary data. The segment boundary is along the coastline of Pelintung Village which is divided into 17 segments. The coastal area of the eastern part of Pelintung Village is categorized as very vulnerable because the physical parameters, namely geomorphology, elevation, shoreline changes, tides, sea level rise, and dominant waves have the highest MCA values. In the socio-economic parameters, land use and population density are also vulnerable because population settlements and dominant activities are located in the coastal area of Pelintung Village.